The Effect of Ratio of Starfruit with Pumpkin Pulps and Concentration of Sodium Benzoate on Quality of Startfruit Sauce - Khasya Rahmi Sitompul; Ismed Suhaidi; Terip Karo-Karo (Universitas Sumatera Utara, 2015)
The aim of this research was to determine the effect of ratio of starfruit with pumpkin pulps and concentration of sodium benzoate on the quality and sensory test of starfruit sauce. This research was using factorial Completely Randomized Design (CRD) with two factors, i.e :ratio of starfruit with pumpkin pulps (P)(90:10%, 85:15%, 80:20%, 75:25%) and concentration of sodium benzoate (S) (0, 0,1, 0,2, 0,3%). The analyzed parameters were water content (%), ash content (%), total microbes (Log CFU/g), total acid (%), vitamin C content (mg/100 g sample), total soluble solid (oBrix), pH, viscosity, and organoleptic value (colour, aroma, and taste). The result showed that ratio starfruit with pumpkin pulps had highly significant effect on water content (%), total microbes (Log CFU/g), total acid (%), vitamin C content (mg/100 g sample), total soluble solid (oBrix), pH, viscosity, and organoleptic values (colour, aroma, and taste). The concentration of sodium benzoate had highly significant effect on water content (%), ash content (%), total microbes (Log CFU/g), total acid (%), vitamin C content (mg/100 g sample), total soluble solid (oBrix), pH, viscosity, and organoleptic value of colour; and had no effect on organoleptic value of aroma and taste and hedonic taste. The interaction of the two factors had highly significant effect on total microbes (Log CFU/g) and had significant effect on organoleptic value of colour. The best treatment which gave the best effect on starfruit sauce was 90:10% of starfruit with pumpkin pulps and 0,2% sodium benzoat. Keyword:Pumpkin, sauce, sodium benzoate, starfruit